Advances in preventive vaccine development against HTLV-1 infection: A systematic review of the last 35 years - Santana, Carolina Souza; Andrade, Felipe de Oliveira; da Silva, Greice Carolina Santos; Nascimento, Jéssica Oliveira de Souza; Campos, Raissa Frazão; Giovanetti, Marta; Santos, Luciane Amorim; Gois, Luana Leandro; Alcantara, Luiz Carlos Júnior; Barreto, Fernanda Khouri (Frontiers in Immunology, 2023)
The Human T-lymphotropic virus type 1 (HTLV-1) was the first described human retrovirus. It is currently estimated that around 5 to 10 million people worldwide are infected with this virus. Despite its high prevalence, there is still no preventive vaccine against HTLV-1 infection. It is known that vaccine development and large-scale immunization of the population play an important role in global public health. To understand the advances in this field we performed a systematic review of the progress achieved in the development of a preventive vaccine against HTLV-1 infection. This review followed the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA®) guidelines and was registered with the International Prospective Register of Systematic Reviews (PROSPERO). The search for articles was performed in PubMed, Lilacs, Embase and SciELO databases. From the 2485 articles identified, 25 were selected according to the inclusion and exclusion criteria. The analysis of these articles indicated that there are potential vaccine designs in development, although there is still a paucity of studies in the human testing phase. Although HTLV-1 was discovered almost 40 years ago, it remains a great challenge and a worldwide neglected infection. The scarcity of funding contributes decisively to the inconclusiveness of vaccine development. The data here summarized intends to bring light the necessity to improve the knowledge regarding this neglected retrovirus, encouraging more studies on the development of vaccines against HTLV-1 with the aim to eliminate the virus as a human threat.